Evaluating Impact: A Comparison of Learning Experiences and Outcomes of Students Completing A Traditional Versus Multidisciplinary, Project-Based Introductory Statistics Course - Lisa, Dierker; Kristin, Flaming; Jennifer L., Cooper; Karen, Singer-Freeman; Kaori, Germano; Jennifer, Rose (International Journal of Education, Training and Learning, 2018)
The teaching of statistics is limited by numerous challenges that are not easily overcome with traditional pedagogical approaches. To evaluate the potential impact of a multidisciplinary, project-based course in introductory statistics, this article examines differences in course experiences, confidence, and interest in future experiences with data analysis and applied statistics of students enrolling in a traditional introductory statistics course compared to a multidisciplinary, project-based course. Results demonstrated that students enrolled in the project-based course had more positive course experiences, showed a greater likelihood of increases in confidence in managing data (e.g. setting aside missing data, creating scales and/or dichotomizing variables), choosing the correct statistical test, and writing syntax or code to run statistical analyses. They also showed greater interest in pursuing additional course-work in statistics and related topics. Findings were not better accounted for by differences in background characteristics of the students enrolled in the traditional vs. project-based course.